Recovering historical memory: a struggle against silence and forgetting? : The politics of victimhood in Spain - Druliolle, Vincent (International journal of transitional justice, 2015)
This article analyzes Spain’s reluctance to deal with its dictatorial past. While the transitional justice literature has focused on the transition to democracy and its legacy or ideological and political factors, I highlight the importance of the definition of victimhood, or the identity, meaning and status of victims in a given society. After briefly reviewing how the literature has studied victims, I outline a theoretical framework to analyze the politics of victimhood, a political struggle that tends to produce a hierarchy of victims. The framework is then applied to the Spanish case to assess the claim by Franco’s victims that they are ‘second-class victims.’ The conclusion underlines the importance of analyzing the politics of victimhood for transitional justice and contends that it should not be limited to the victim-perpetrator dichotomy in relation to a given episode of past violence. It also stresses some of the challenges that a critical analysis of victimhood and victims raises.